Investigation on Fluid Flow inside a Continuous Slab Casting Mold Using Particle Image Velocimetry. Issue 11 (30th July 2019) - Ren, Lei; Ren, Ying; Zhang, Lifeng; Yang, Jichun
Abstract : Herein, full region (not divided the mold into several parts) fluid flow in a wide slab mold is studied using a one‐quarter scale water model. The particle image velocimetry (PIV) is used to analyze the turbulent features of the flows. The features include the distribution of instantaneous velocity fields, time‐averaged velocity fields, turbulent fluctuation velocity fields, the turbulent kinetic energy (TKE) and its dissipation rate, rate of strain, and the vorticity. There are several ﬁndings in this study. The fluid flow in the mold is not always symmetrical even the submerged entry nozzle (SEN) is strictly centered, but the time‐averaged flow structure is symmetric flow. The development of turbulence is relatively sufficient in the lower part of the mold, where the flow velocity is large, and the TKE and its dissipation rate are also large. Regions of positive and negative values signify the direction of the flow rotation with mirror images on both sides of the SEN. The regions of high vorticity are close to jets and decrease as it flows further into the mold. Abstract : Full region fluid flow in a wide slab mold is studied using a one‐quarter scale water model. The particle image velocimetry is used to analyze the turbulent features of the flows. The features include the instantaneous velocity fields, time‐averaged velocity fields, fluctuation velocity fields, the turbulent kinetic energy (TKE), TKE dissipation rate, rate of strain, and the vorticity.